Long noncoding RNA CDKN2B‐AS1 interacts with transcription factor BCL11A to regulate progression of cerebral infarction through mediating MAP4K1 transcription. Issue 6 (14th March 2019) - Lei, Jun-Jie; Li, Hui-Qing; Mo, Zhi-Huai; Liu, Ke-Jia; Zhu, Ling-Juan; Li, Chun-Yi; Chen, Wen-Li; Zhang, Lei
ABSTRACT: The effective therapeutic approach of cerebral infarction is limited because of its underlying complexity. Recently, multiple long noncoding RNAs (lncRNAs) have been identified in the pathogenesis of cerebral infarction. Here, the current study aims to explore the interaction among lncRNA cyclin‐dependent kinase inhibitor‐2B–antisense RNA 1 (CDKN2B‐AS1), transcription factor B‐cell lymphoma/leukemia 11A (BCL11A), and MAPKK kinase kinase 1 (MAP4K1) and further investigate whether they affect cerebral infarction progression. The expression of CDKN2B‐AS1, BCL11A, and MAP4K1 was altered in lymphocytes extracted from patients with cerebral infarction. In order to identify their roles in regulatory T (Treg ) cells, the proliferation and apoptosis of the CD4 + CD25 + Treg cells were examined, and levels of IL‐4, IL‐10, and TGF‐β were determined. Also, the RNA crosstalk among CDKN2B‐AS1, BCL11A, and MAP4K1 was validated. Finally, we established a rat model of middle cerebral arterial occlusion to evaluate the neurologic impairment and cerebral infarction volume. The results revealed that lymphocytes in patients with cerebral infarction presented with the up‐regulated expression of CDKN2B‐AS1. Moreover, BCL11A could specifically bind to CDKN2B‐AS1 and MAP4K1 promoter so as to inhibit MAP4K1. Moreover, it was observed that down‐regulated CDKN2B‐AS1 inhibited CD4 + CD25 + Treg ‐cell proliferation, reduced levels of IL‐4, IL‐10, and TGF‐β and cerebral infarction volume, and elevated MAP4K1 expression. Collectively, our study provides evidence that CDKN2B‐AS1 silencing could increase MAP4K1 expression to inhibit the CD4 + CD25 + Treg ‐cell proliferation by reducing enrichment of transcription factor BCL11A, thereby protecting against cerebral infarction progression, highlighting a promising therapeutic strategy for treating cerebral infarction.—Lei, J.‐J., Li, H.‐Q., Mo, Z.‐H., Liu, K.‐J., Zhu, L.‐J., Li, C.‐Y., Chen, W.‐L., Zhang, L. Long noncoding RNA CDKN2B‐AS1 interacts with transcription factor BCL11A to regulate progression of cerebral infarction through mediating MAP4K1 transcription. FASEB J. 33, 7037–7048 (2019). www.fasebj.org